2021
DOI: 10.1111/1365-2664.13946
|View full text |Cite
|
Sign up to set email alerts
|

Organic farming supports lower pest infestation, but fewer natural enemies than flower strips

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Hence, organically fertilized plants can be the worst host of herbivores, and this might be the cause of lower pest infestation in organic cotton. Many previous studies also reported lower herbivore infestations in organically managed systems as compared to synthetically fertilized systems (Arancon et al, 2005;Birkhofer, Bezemer, et al, 2008;Török et al, 2021). Additionally, manure application augments microbial activity in association with organic matter and provides a buffering capability to maintain nutrients and minerals balance in plants (mineral balance hypothesis), can improve nutrient retention and uptake by plants, which in turn can support the plant growth, vigour and affect the performance of herbivores Phelan et al, 1996).…”
Section: Discussionmentioning
confidence: 94%
“…Hence, organically fertilized plants can be the worst host of herbivores, and this might be the cause of lower pest infestation in organic cotton. Many previous studies also reported lower herbivore infestations in organically managed systems as compared to synthetically fertilized systems (Arancon et al, 2005;Birkhofer, Bezemer, et al, 2008;Török et al, 2021). Additionally, manure application augments microbial activity in association with organic matter and provides a buffering capability to maintain nutrients and minerals balance in plants (mineral balance hypothesis), can improve nutrient retention and uptake by plants, which in turn can support the plant growth, vigour and affect the performance of herbivores Phelan et al, 1996).…”
Section: Discussionmentioning
confidence: 94%
“…Predators such as syrphids and lacewings consume flower resources (nectar and pollen) as adults, whereas many other species display facultative consumption of these resources, relying on these as alternative food sources (Lundgren, 2009). Therefore, many studies reported that increasing flowering plants resulted in lower crop damage levels by herbivore arthropods via predator enhancement (Bischoff et al, 2016; Pollier et al, 2018; Török et al, 2021; Zytynska et al, 2021). Many parasitoids also feed on flowers as adults, and although our analysis did not show a significant link between this guild and any vegetation trait, all variables showed a positive trend.…”
Section: Discussionmentioning
confidence: 99%
“…However, not all neighboring plants are useful, since certain species enhance the presence of cereal aphids. For instance, flower strips in-between fields increased the abundance of cereal aphids [244]. However, wildflower strips enhanced aphid parasitism and predation [245].…”
Section: Effect Of Agricultural Practices and Environmentmentioning
confidence: 99%